Strategi Komunikasi Inokulatif Sherly Tjoanda dalam Merespons Isu Tambang pada Konten Youtube KOMPAS TV Program ROSI - Fanisa Oktafia Ningrum; Rila Setyaningsih (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
Public criticism toward extractive industries has increasingly placed public officials under intense media scrutiny, requiring strategic communication responses to maintain credibility and public trust. This study examines the inoculative communication strategy employed by Sherly Tjoanda in responding to mining-related issues during her appearance on the ROSI program aired by Kompas TV. The research aims to identify the forms and patterns of inoculation strategies used in addressing public criticism. Using a qualitative content analysis approach, data were collected through documentation and transcription of relevant interview segments and analyzed using Inoculation Theory as the main analytical framework. The findings reveal three dominant elements of inoculative communication: supportive arguments, anticipation of criticism, and refutation of criticism. These elements are manifested through rational reasoning, legal legitimacy, empathetic acknowledgment, preventive defense, and argumentative rebuttals. The results indicate that the communication strategy combines supportive and refutational defenses to reinforce position consistency while reducing the persuasive impact of opposing narratives. This study contributes to the development of political communication research by demonstrating how inoculation theory operates in mediated political discourse and offers practical insights into managing public criticism in controversial policy contexts.